Pengaruh Aromaterapi Lemon pada Postpartum - Nurlaili, Siti; Marsum, Marsum; Widyawati, Melyana Nurul (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
The postpartum period is the period that starts after the birth of the placenta and ends when the womb returns to its normal state as before pregnancy, which lasts for 6 weeks or 42 days and is a period where the mother experiences various problems and changes in mood, so an innovation is needed that improves the mood. mothers get better, one of which is by giving lemon aromatherapy. The aim of this study was to determine the effect of lemon aromatherapy on postpartum. This study was a literature review, with a search using Evidence Based Practice (EBP) from one database, namely Google Scholar. The search was carried out using PICO filtering, resulting in 8 articles that met the inclusion criteria for synthesis. The synthesis results showed that lemon aromatherapy had an effect in the postpartum period, including reducing pain levels, reducing anxiety, reducing fatigue, increasing breast milk production and quality of life and reducing the risk of potpartum blues. Furthermore, it was concluded that giving lemon aromatherapy had a positive effect on the health of postpartum mothers.Keywords: aromatherapy; lemon; postpartum mother ABSTRAK Masa nifas adalah masa yang dimulai dari setelah kelahiran plasenta dan berakhir ketika alat kandungan kembali semula seperti sebelum hamil, yang berlangsung selama 6 minggu atau 42 hari dan merupakan masa di mana ibu merasakan berbagai masalah dan perubahan mood, sehingga dibutuhkan suatu inovasi yang membuat suasana hati ibu menjadi lebih baik, salah satunya adalah dengan pemberian aromaterapi lemon. Tujuan dari studi ini adalah untuk mengetahui pengaruh aromaterapi lemon pada postpartum. Studi ini merupakan tinjauan literatur, dengan pencarian menggunakan Evidence Based Practice (EBP) dari satu database yaitu Google Scholar. Pencarian dilakukan dengan penyaringan PICO, sehingga didapatkan 8 artikel yang sesuai dengan kriteria inklusi untuk dilakukan sintesis. Hasil sintesis menunjukkan bahwa aromaterapi lemon berpengaruh pada masa postpartum antara lain menurunkan tingkat nyeri, mengurangi kecemasan, mengurangi kelelahan, meningkatkan produksi ASI dan kualitas hidup serta menurunkan resiko potpartum bluess. Selanjutnya disimpulkan bahwa pemberian aromaterapi lemon berpengaruh positif pada kesehatan ibu nifas.Kata kunci: aromaterapi; lemon; ibu nifas